Evaluation of surgical complications in patients undergoing anterior cruciate ligament reconstruction surgery (Research, Society and Development, 2021)
Objectives: To analyze the surgical complications of patients undergoing anterior cruciate ligament reconstruction surgery, checking the profile of the patients. Methods: It consists of a systematic review of the literature whose guiding question is “In patients undergoing anterior cruciate ligament reconstruction surgery, does the use of this surgical treatment, in comparison with any treatment, cause complications?”. To elaborate the study, a search was carried out in the databases US National Library of Medicine National Institutesof Health (PUBMED), Virtual Health Library (VHL), Sciencedirect and Word Wide Science and the election of the eligibility criteria followed only publications that are Randomized Clinical Trials and that fit the proposed theme. In sequence, from the reading of the titles and subsequent analysis of the abstracts, the final sample consisted of 6 publications. Results: It was found that the most common complications found in the reconstruction of the anterior cruciate ligament are knee pain, kinematic changes during gait, cartilage degeneration, infections, deficit in knee flexion, graft failure, ligament laxity and hemarthrosis. The general profile of patients found in the studies was an average age of 25.8 years, a number of 290 men, representing 58% of the participants, and a number of 210 women, categorizing 42% of the patients. Conclusion: It is observed in the studies that regardless of the surgical method used, which varies by the type of graft used, which may be allograft or autograft, and by the type of screw used, which may be bioabsorbable or metal, surgical complications are present.